Amalgam Tattoo - A Review - P. , Kuzhalvaimozhi; Priscilla Antony, Delphine; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Amalgam is one of the most versatile materials used in dentistry and used as a restorative material for past 150 years. Amalgam has various constituents such as silver, tin, zinc and mercury-a toxic constituent. It produces harmful effects in the body, by passing through cell membrane, cross blood brain barrier and enters central nervous system and cause immunological and psychological problems. Amalgam tattoo results from inadvertent deposition of amalgam within oral mucosa and alveolar bone during dental procedures. Overtime, metallic particles from dental amalgam leach into soft tissue causing discoloration.